Evaluation of testicular volume in children aged 8-17 years in south India - Boben, Gissy Elizabeth; Umapathy, P; Ravichandran, Latha; Godfrey, D A; Ramani, Gokul; Srinivasan, V (Indian Journal of Child Health, 2016)
Background: The standard five-stage clinical systems of Tanner and Marshall for assessing pubertal development are limited by observer variations. The measurement of testicular volume, in addition, will make assessments objective. It is important to determine the mean testicular volumes (MTVs) for a given population as reference standards. Aim: To determine the MTVs in children between 8 and 17 years and to compare the MTV with Tanners staging. Methods: A cross-sectional study was conducted on 750 healthy school boys from 2 schools in Chennai between 8 and 17 years of age by a single observer to reduce the observer variation. Tanner’s staging and testicular volume measurement were done using a Prader’s orchidometer. Results: Of the 750 boys studied, the MTV of both the right and left testes was found to increase from 2.47±0.70 cc at 8 years of age, to 3.84±1.91 cc at 12 years, to 15.93±6.65 cc at 17 years of age (p=0.0001). The mean age was found to be increased from 12.69 years at sexual maturity rating (SMR) Stage-2, to 15.66 years at SMR Stage-5. We found a significant positive correlation between SMR and height (p=0.0001), weight (p=0.0001) and body mass index (p=0.0001). The average size of both the right and left testes was found to be increased from 2.86±1.12 cc at SMR Stage-1 to 12.51±4.67 cc at SMR Stage-3 to 18.90±4.64 cc at SMR Stage-5. In our study, 0.5% (n=4) had an MTV of 4 cc at the age of 8, 0.4% (n=3) had an MTV of <4 cc by the age of 14. Conclusion: The measurement of MTV along with Tanner’s SMR staging makes the assessment of male genital development more objective and acts as a measure of testicular growth and spermatogenesis. Generating a baseline data on age appropriate testicular volume in a population or ethnic group is essential to assess sexual developmental disorders among males.